PELATIHAN KERAJINAAN TANGAN PIRING LIDI SAWIT DALAM MENINGKATKAN KREATIVITAS MASYARAKAT MANDIRI DESA BINTANG SELATAN - M Bima Eka Putra; Nour Farozi; Sudriyanti Putri; Solichin Solichin; Herry Novrianda (STIA Bengkulu, 2023)
The people of Bintang Selatan Village mostly work as rubber farmers and oil palm farmers. During the palm oil harvest period, palm leaf fronds are always wasted, even though palm leaf fronds can be used as a work that has selling value. So it is necessary to carry out socialization to foster community creativity so that it can innovate the community to become an independent society. It is necessary to practice making dishes from palm sticks, it takes perseverance and a touch of creativity and patience. As for handicrafts for high selling value, innovation is needed in order to attract interested people to buy, and can create Small and Medium Enterprises in South Star Village.